2010
DOI: 10.1128/jvi.00754-10
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of APOBEC3H Variants in HIV-1 Virions Determines Their Antiviral Activity

Abstract: Several members of the human APOBEC3 family of cytidine deaminases can potently restrict retroviruses such as HIV-1. The single-domain APOBEC3H (A3H) is encoded by four haplotypes, of which only A3H haplotype II-RDD (hapII-RDD) restricts HIV-1 efficiently. The goal of this study was to elucidate the mechanisms underlying the differences in antiviral activity among A3H haplotypes. The naturally occurring A3H hapI-GKE and hapII-RDD variants differ at three amino acid positions. A panel of six site-directed mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 50 publications
7
61
1
Order By: Relevance
“…4B). Thus, we conclude that A3H binds HIV-1 NC in an RNA-dependent manner, which is consistent with a recent study (29). Next, we determined whether A3H contains a similar YYFW motif that serves as the packaging signal.…”
Section: Genotype and Haplotype Analysis Of The Human A3h Genesupporting
confidence: 75%
See 2 more Smart Citations
“…4B). Thus, we conclude that A3H binds HIV-1 NC in an RNA-dependent manner, which is consistent with a recent study (29). Next, we determined whether A3H contains a similar YYFW motif that serves as the packaging signal.…”
Section: Genotype and Haplotype Analysis Of The Human A3h Genesupporting
confidence: 75%
“…Recently, Ooms et al reported that although A3H hap I protein was poorly expressed in cells, it could be still packaged efficiently into HIV-1 virions. They also presented evidence that A3H hap I specifically interacted with MA-CA other than NC for virion packaging (29). We found that A3H hap I was poorly packaged into virions because it was not expressed in the cell, and, therefore, we cannot confirm this observation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A 63 K-linked poly-Ub chain on Gag or a cellular protein in the vicinity of the emerging viral bud is necessary to stimulate virus release (73,74). HIV may take advantage of 63 K-linked poly-Ub A3H, which can associate with Gag through an RNA intermediate or directly (75), to promote virus release. This may aid in virus budding and titrate out the effect of the A3H during viral adaptation akin to how Vif mutants unable to degrade A3G can acquire mutations that enable the production of more virus particles to minimize A3G packaging (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…The first family member to be recognized for this activity, APOBEC3G (A3G), was identified on account of being the cellular target for the human immunodeficiency virus type 1 (HIV-1) regulatory protein Vif (5), a feature that is also shared by APOBEC3D (A3D) (6,7), APOBEC3F (A3F) (8)(9)(10)(11) and haplotypes II, V, and VII of APOBEC3H (A3H) (12)(13)(14). In the context of HIV-1 infection, the current weight of evidence indicates that A3G may exert the more potent antiviral effect, with A3D, A3F, and A3H eliciting less pronounced effects, though this continues to be debated.…”
mentioning
confidence: 99%